Continuous skill assessment form (Part 1) - Md Mustafa, Md Muziman Syah; Ahmad, Norsham (2020)
This continuous skill assessment form (Part 1) is developed as a tool to evaluate Optometry students' performance in conducting routine optometric tests and interpreting the results of the tests in Primary Optometry Clinic I, II, and III. It includes history taking, vision and visual acuity, cover test, Hirschberg, pupil assessment, stereopsis, colour vision tests/ procedures